EXPLORING THE ASSOCIATION BETWEEN VITAMIN D AND URINARY TRACT INFECTION RISK - A REVIEW OF LITERATURE - Banasik, Mateusz; Adamczyk, Aleksandra; Gunia, Katarzyna; Grylowska, Gabriela; Paluch, Anna; Rebizant, Marcin; Żak, Agata; Palak, Andrzej; Ignatowicz, Anna; Tryba, Michał (International Journal of Innovative Technologies in Social Science, 2026)
Urinary tract infection (UTI) represents one of the most prevalent bacterial infections worldwide. Emerging evidence suggests that vitamin D status may play a significant role in modulating susceptibility to UTI. This review article examined the available scientific literature concerning the association between serum 25-hydroxyvitamin D [25(OH)D] concentrations and the risk of UTI across diverse patient populations, including children, adults, pregnant women, and renal transplant recipients. The overwhelming majority of reviewed studies consistently demonstrated significantly lower serum 25(OH)D concentrations in patients with UTI compared to healthy controls. Serum 25(OH)D levels below 20 ng/mL were identified as a significant independent risk factor for UTI occurrence. The association was particularly pronounced in women and in the pediatric population.The potential biological mechanisms underlying this relationship were also discussed, including the role of calcitriol in activating immune cells, stimulating the production of antimicrobial peptides - such as cathelicidin and defensins - modulating pro-inflammatory cytokine expression, and reinforcing epithelial barrier integrity. Functions and metabolism of vitamin D were reviewed, emphasizing its classical role in calcium homeostasis as well as its non-classical immunomodulatory actions. Vitamin D deficiency was identified as a modifiable risk factor that may be cost-effectively addressed through appropriate sun exposure and supplementation strategies. However, further well-designed, large-scale randomized controlled trials are warranted to establish causality and to determine whether correction of vitamin D deficiency can effectively prevent urinary tract infections.